A taxonomic revision of the genus Brookea (Plantaginaceae) - Neo, Louise; Huurne, Suzanne Ter; Adema, Frits (Phytotaxa, 2019)
The genus Brookea is revised and six species are recognised. Three species are endemic to Borneo, and two new species are here described that are only known from Sulawesi, B. celebica and B. linduensis. One species, B. albicans, was previously thought to be endemic to Borneo, but has now been newly recorded for Sulawesi. Two species are lectotypified, all species are described, and a key to the species is provided.